2003
DOI: 10.1002/prop.200310090
|View full text |Cite
|
Sign up to set email alerts
|

Intersecting branes, defect conformal theories and tensionless strings

Abstract: The defect conformal field theory describing intersecting D3-branes at a C 2 /Z k orbifold is used to (de)construct the theory of intersecting M5-branes, as well as M5-branes wrapping the holomorphic curve xy = c. The possibility of a 't Hooft anomaly due to tensionless strings at the intersection is discussed. This note is based on a talk given by Zachary Guralnik at the 35th International Symposium Ahrenshoop on the Theory of Elementary Particles.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2004
2004

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…For details of this deconstruction please see Sec. 4.4 which is based on [118,119]. We will study further the defect conformal field theory associated with two stacks of D3-branes intersecting each other over a 1+1-dimensional subspace.…”
Section: Deconstruction Of Extra Dimensionsmentioning
confidence: 99%
“…For details of this deconstruction please see Sec. 4.4 which is based on [118,119]. We will study further the defect conformal field theory associated with two stacks of D3-branes intersecting each other over a 1+1-dimensional subspace.…”
Section: Deconstruction Of Extra Dimensionsmentioning
confidence: 99%
“…(14) into the action of null-super-p-brane in the usual D = 3, 4, 6, 10 superspaces (see [29] for D=4) by substituting Γ αβ µ Π µ m ≡ Γ αβ µ (∂ m x µ − i∂ m θΓ µ θ) for Π αβ m . Tensionless strings and p-branes in usual spacetime and usual superspace were discussed many times in the context of superstring/M-theory [33]- [36], [29], [37]- [43] (see [29,41] for more references). In particular, they appear as singularities in K3 compactification of superstring theory down to six dimensions which connect all known supersymmetric six dimensional vacua [39].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the earliest studies of such impurity field theories may be found in [24,25,26]. In many instances, this theory is a non-trivial defect conformal field theory [27,28,29,4,5,6,7]), or dCFT. In this section we review the superspace description of defect field theories and expand upon some results [5] concerning the Higgs branch of the dCFT describing intersecting D3-branes.…”
Section: Holomorphic Curves From Intersecting Branes Preserving Eightmentioning
confidence: 99%
“…This superspace may also be used to described the fields in the ambient space which are not localized at the impurity. The formalism in which degrees of freedom in higher dimensions are described in a lower-dimensional superspace was developed originally in [2,3] and has been applied to study a number of theories, including the defect conformal theories which arise for systems of interesecting branes [4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%